Synergistic effect of insulation and liquid cooling on mitigating the thermal runaway propagation in lithium-ion battery module. (25th November 2021) - Rui, Xinyu; Feng, Xuning; Wang, Hewu; Yang, Huiqian; Zhang, Youqun; Wan, Mingchun; Wei, Yaping; Ouyang, Minggao
Highlights: 3D thermal runaway propagation (TRP) models with liquid cooling are established. Overheating abuse tests are conducted and validates the models. The synergistic effect of dissipation and insulation on TRP is investigated. The TRP boundary is concluded from the modeling analysis. The criticality boundary can guide the thermal safety design of the BTMS. Abstract: Electric vehicles (EVs) occasionally experience accidents caused by the thermal runaway propagation (TRP) of Li-ion batteries. Countermeasures for TRP through battery thermal management systems have typically been conducted by enhancing heat dissipation or thermal insulation individually, without considering their coupled effects. In this study, the synergy of heat dissipation underneath the battery module with thermal insulation between adjacent cells was investigated through experiments and simulations for TRP elimination. Simulations of the heat flux were conducted based on a 3D model, and the results agreed well with the failure behavior in the experiments. The results indicate that pure liquid cooling fails to mitigate the TRP of a prismatic battery module because the heat flux between a thermal runaway cell and its neighbor is difficult to attenuate by cooling plate placed underneath, which only reduces it from 885.7 to 848.2 W. Furthermore, the insulation provides more time for the heat to be drained through the cooling plate; therefore, successful TRP inhibition requires the cooperation of thermal insulation and liquid cooling. Six critical conditions under which no TRP occurs and a theoretical diagram regarding the nexus of heat dissipation and thermal insulation were obtained from the modeling analysis. Finally, a universal criterion was proposed to optimize the design of thermal insulation and heat dissipation in a battery module, providing insight into the thermal safety design of EVs.